2021
DOI: 10.3390/nu13010152
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Effects of Magnesium Oxide and Inulin on Intestinal Microbiota and Cecal Short-Chain Fatty Acids

Abstract: Constipation is a common condition that occurs in many people worldwide. While magnesium oxide (MgO) is often used as the first-line drug for chronic constipation in Japan, dietary fiber intake is also recommended. Dietary fiber is fermented by microbiota to produce short-chain fatty acids (SCFAs). SCFAs are involved in regulating systemic physiological functions and circadian rhythm. We examined the effect of combining MgO and the water-soluble dietary fiber, inulin, on cecal SCFA concentration and microbiota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…Del Chierico et al showed that magnesium can alleviate colitis in mice by increasing short-chain fatty acids (SCFA) and reducing the number of bacteria involved in inflammation [123]. Omori et al in a study in mice showed that MgO along with inulin administration increased intestinal pH but also decreased levels of SCFA and lactic acid [124]. Intestinal bacteria such as Lactobacillus spp.…”
Section: Effect Of Magnesium On Gut Microbiotamentioning
confidence: 99%
“…Del Chierico et al showed that magnesium can alleviate colitis in mice by increasing short-chain fatty acids (SCFA) and reducing the number of bacteria involved in inflammation [123]. Omori et al in a study in mice showed that MgO along with inulin administration increased intestinal pH but also decreased levels of SCFA and lactic acid [124]. Intestinal bacteria such as Lactobacillus spp.…”
Section: Effect Of Magnesium On Gut Microbiotamentioning
confidence: 99%
“…Magnesium: There is some evidence that magnesium orotate may modulate the microbiome-gut-brain axis and that this, combined with probiotic supplementation, may improve some aspects of gastrointestinal and psychiatric disorders that are associated with dysbiosis [84]. In a rodent-based study, it was shown that the addition of magnesium oxide to an inulin-based diet resulted in significant changes to gut microbiota composition and caecal SCFAs [85]. In a further rodent-based study, it was shown that magnesium deficiency within the diet altered gut microbiota and was associated with altered anxiety-like behaviour [86].…”
Section: The Effects Of the MD On Gut Microbiotamentioning
confidence: 99%
“…Unlike stimulant laxatives, MgO was thought not to lose its efficacy with continuous use, but in some cases, long-term administration of MgO has worsened defecation [6]. Recent animal experiments have shown that dietary fiber is fermented by intestinal bacteria to produce short-chain fatty acids (SCFAs), which improve the intestinal environment and chronic constipation, but this constipation-improving effect disappeared when MgO was used [7]. The mechanism by which MgO eliminates this constipation-improving effect is an increase in intestinal pH together with a concomitant change in the composition of the intestinal microbiota and a 5 decrease in the production of SCFAs [7].…”
mentioning
confidence: 99%
“…Recent animal experiments have shown that dietary fiber is fermented by intestinal bacteria to produce short-chain fatty acids (SCFAs), which improve the intestinal environment and chronic constipation, but this constipation-improving effect disappeared when MgO was used [7]. The mechanism by which MgO eliminates this constipation-improving effect is an increase in intestinal pH together with a concomitant change in the composition of the intestinal microbiota and a 5 decrease in the production of SCFAs [7]. On the other hand, the guidelines for chronic constipation place probiotics at a recommendation level of 2 and a level of evidence of B [5].…”
mentioning
confidence: 99%